Conjugates of Chloramphenicol Amine and Berberine as Antimicrobial Agents - Julia A. Pavlova; Andrey G. Tereshchenkov; Pavel A. Nazarov; Dmitrii A. Lukianov; Dmitry A. Skvortsov; Vladimir I. Polshakov; Byasilya F. Vasilieva; Olga V. Efremenkova; Mikhail Y. Kaiumov; Alena Paleskava; Andrey L. Konevega; Olga A. Dontsova; et al. (MDPI AG, 2022)
In order to obtain antimicrobial compounds with improved properties, new conjugates comprising two different biologically active agents within a single chimeric molecule based on chloramphenicol (CHL) and a hydrophobic cation were synthesized and studied. Chloramphenicol amine (CAM), derived from the ribosome-targeting antibiotic CHL, and the plant isoquinoline alkaloid berberine (BER) are connected by alkyl linkers of different lengths in structures of these conjugates. Using competition binding, double reporter system, and toeprinting assays, we showed that synthesized CAM-Cn-BER compounds bound to the bacterial ribosome and inhibited protein synthesis like the parent CHL. The mechanism of action of CAM-C5-BER and CAM-C8-BER on the process of bacterial translations was similar to CHL. Experiments with bacteria demonstrated that CAM-Cn-BERs suppressed the growth of laboratory strains of CHL and macrolides-resistant bacteria. CAM-C8-BER acted against mycobacteria and more selectively inhibited the growth of Gram-positive bacteria than the parent CHL and the berberine derivative lacking the CAM moiety (CH3-C8-BER). Using a potential-sensitive fluorescent probe, we found that CAM-C8-BER significantly reduced the membrane potential in B. subtilis cells. Crystal violet assays were used to demonstrate the absence of induction of biofilm formation under the action of CAM-C8-BER on E. coli bacteria. Thus, we showed that CAM-C8-BER could act both on the ribosome and on the cell membrane of bacteria, with the alkylated berberine fragment of the compound making a significant contribution to the inhibitory effect on bacterial growth. Moreover, we showed that CAM-Cn-BERs did not inhibit eukaryotic translation in vitro and were non-toxic for eukaryotic cells.